2019
DOI: 10.1007/s11191-019-00086-6
|View full text |Cite
|
Sign up to set email alerts
|

Examining Reasoning Practices and Epistemic Actions to Explore Students’ Understanding of Genetics and Evolution

Abstract: Examining reasoning practices and epistemic actions to explore students' understanding of genetics and evolution Abstract This paper focuses on students' discursive moves and reasoning practices while engaged in a task that requires making explanatory links between sickle cell disease and malaria. Both diseases pertain to key areas of the biology curriculum, namely, genetic variability and natural selection, and are connected to the theory of evolution of living organisms. Specifically, this study examines the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…This study adopts a qualitative case-study approach and draws upon discourse analysis as a method for analysing the discursive and rhetorical functions of modelling, understood as a repertoire of students' biological thinking (Ageitos et al, 2019;Brigandt, 2020). The study runs as a longitudinal project over two school years (2014)(2015)(2016), focussing on learning genetics and evolution through modelling and argumentation practices.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…This study adopts a qualitative case-study approach and draws upon discourse analysis as a method for analysing the discursive and rhetorical functions of modelling, understood as a repertoire of students' biological thinking (Ageitos et al, 2019;Brigandt, 2020). The study runs as a longitudinal project over two school years (2014)(2015)(2016), focussing on learning genetics and evolution through modelling and argumentation practices.…”
Section: Contextmentioning
confidence: 99%
“…It may be helpful to make explicit connections in the classroom relating the disciplines needed to enrich students' understanding of evolution, such as genetics and bio-geography, geology and history. This leads to a second implication: for biology education to embrace a plurality of interpretational frameworks, including recent calls for the active use of openended concepts (Brigandt, 2020) to support understanding of complex processes, which are dynamic and multi-levelled, such as evolution; and for genetics and evolution to be taught together, through processes that engage students in connecting both domains (Ageitos et al, 2019).…”
Section: Conclusion Educational Implications and Limitationsmentioning
confidence: 99%
“…For many countries, such as the United States, the United Kingdom, and Taiwan, Mendelian genetics is one of the main topics of biology in school science. However, researchers have unanimously found that genetics is conceptually di cult to learn and teach (Ageitos et al, 2019;Cavallo, 1996;Cho et al, 1985;Duncan et al, 2009;Lewis & Wood-Robinson, 2000;Stewart, 1988). Studies showed that some students have di culty forming conceptual relationships between alleles and cell processes like mitosis and meiosis because students require multi-level thinking and reasoning (Lewis & Wood-Robinson, 2000;Tsui & Treagust, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 There are many reasons why both teachers and students find teaching of the theory confusing sometimes. 4,5 In our proposal, we deal with two of them: terms/concepts as well as the understanding of the evolution mechanism. Moreover, the starting point of our approach lies in the molecular level of biology, in discussing and analyzing the genetic characteristics of a virtual world.…”
Section: Introductionmentioning
confidence: 99%
“…There are many reasons why both teachers and students find teaching of the theory confusing sometimes 4,5 . In our proposal, we deal with two of them: terms/concepts as well as the understanding of the evolution mechanism.…”
Section: Introductionmentioning
confidence: 99%